Způsoby integrace v životních příbězích ukrajinských žen v České republice. - Popová, Irena (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2023)
The objective of the thesis is to show various ways of integration of the women who came to the Czech Republic from Ukraine. I will introduce the life of these Ukrainian women on the basis of their life stories and experience and I will also mention the causes of their migration to a foreign country and the ways of their integration into the Czech society. Nowadays, it is a very discussed topic and I as a future social worker can play a very important role in the process of the integration of these women. The theoretical part is focused on the elaboration of the findings concerning the social work and social policy connected with foreigners. I also tried to define the terms related to the migration policy. I focused on the history of migration, its reasons and the issues connected with it. The area of my interest also were the myths and prejudices related to the perception of migrants in the Czech Republic. In the practical part, I described the ways of data collection. I especially focused on its evaluation. I investigated the various ways of the integration of the respondents on the basis of their personal experience. I chose women of various age groups. One group of the women came to the Czech Republic in the ninetees. They spent here a longer part of their lives, another group of the women came...